Realities, utopias, and misconceptions concerning the globalisation of literary studies - Neubauer, John (Primerjalna književnost, 2009)
Arjun Appadurai's categories of "grassroots globalisation" ("optical challenge", area studies, and research on globalisation) are applied to recent comparative literary studies: Pascale Casanova's La république mondiale des lettres, Gayatri Spivak's Death of a Discipline, and Franco Moretti's "Conjectures on World Literature".
Keywords: Casanova, Pascale; Spivak, Gayatri; Moretti, Franco; primerjalna literarna veda; svetovna književnost; globalizacija; globalization